Global Evolution of Pathogenic Bacteria With Extensive Use of Fluoroquinolone Agents - Fuzi, Miklos; Rodriguez Baño, Jesus; Toth, Akos (Frontiers in Microbiology, 2020)
It is well-established that the spread of many multidrug-resistant (MDR) bacteria is predominantly clonal. Interestingly the international clones/sequence types (STs) of most pathogens emerged and disseminated during the last three decades. Strong experimental evidence from multiple laboratories indicate that diverse fitness cost associated with high-level resistance to fluoroquinolones contributed to the selection and promotion of the international clones/STs of hospital-associated methicillin-resistant Staphylococcus aureus (HA-MRSA), extended-spectrum β-lactamase-(ESBL)-producing Klebsiella pneumoniae, ESBL-producing Escherichia coli and Clostridioides difficile. The overwhelming part of the literature investigating the epidemiology of the pathogens as a function of fluoroquinolone use remain in concordence with these findings. Moreover, recent in vitro data clearly show the potential of fluoroquinolone exposure to shape the clonal evolution of Salmonella Enteritidis. The success of the international clones/STs in all these species was linked to the strains’ unique ability to evolve multiple energetically beneficial gyrase and topoisomerase IV mutations conferring high-level resistance to fluorquinolones and concomittantly permitting the acquisition of an extra resistance gene load without evoking appreciable fitness cost. Furthermore, by analyzing the clonality of multiple species, the review highlights, that in environments under high antibiotic exposure virulence factors play only a subsidiary role in the clonal dynamics of bacteria relative to multidrug-resistance coupled with favorable fitness (greater speed of replication). Though other groups of antibiotics should also be involved in selecting clones of bacterial pathogens the role of fluoroquinolones due to their peculiar fitness effect remains unique. It is suggested that probably no bacteria remain immune to the influence of fluoroquinolones in shaping their evolutionary dynamics. Consequently a more judicious use of fluoroquinolones, attuned to the proportion of international clone/ST isolates among local pathogens, would not only decrease resistance rates against this group of antibiotics but should also ameliorate the overall antibiotic resistance landscape.